Determinants of Access to Bank Credit by Smallholder Agricultural Households in Uganda: Evidence from UNHS 2019/2020 - Areebahoona, Anthony; Tindimwebwa, Kenneth; Okurut, Francis (East African Journal of Business and Economics, 2024)
Agricultural credit plays a significant role in boosting cash and food crop production for household consumption, domestic and foreign markets. The purpose of this study was to investigate the determinants that affect smallholder farmer’s access to bank credit in Uganda. The study used data from the Uganda National Household Survey 2019/2020 (UNHS). The study utilized a logit regression model for the analysis of data. The findings from the model showed that farmer’s access to bank credit in Uganda was positively and significantly influenced by sex of the household head, income level of the household head, marital status of the household head, age of the household head and ownership of a bank savings account. The study’s conclusions led to the development of key policy recommendations. These include promoting a savings culture through various initiatives, providing incentives such as special savings accounts or matching deposit programs, creating customized banking products to carter to farmers needs and offering free tertiary education to graduates of Universal Primary Education, Universal Secondary Education, and Universal Post O Level Education and Training